Collaborative Governance in Recognizing Customary Law Communities And Customary Communal Land Rights in Kampar Regency - Febrina, Rury; Amin, Raja Muhammad; ', Isril; ', Ishak (Journal of Governance and Public Policy, 2021)
Recognition and protection towards customary law communities in Kampar Regency are inevitable, remembering that the existence of these communities far before the establishment of this nation. A very progressive response was issued by the Regent of Kampar by Forming Registration Team for The Establishment of Customary Law Communities, Customary Territory, and Customary Forests in Kampar Regency. The Registration Team came from local government organizations, national land agencies, academicians, ministries element, non-governmental organization, and customary community institution shows collaboration that involves state actors. This collaboration successfully initiates the acknowledgment toward customary law communities and customary law with the release of Regent Decree in some areas under the Kampar Regency. This study uses a qualitative method with the type of phenomenological research. This collaborative governance is initiated by NGOs that focus on the environment and sustainable development. dominance is still found in the implementation of duties, the unequal power / authority of all parties, conflicts of interest, political will from regional heads and communication and coordination issues are still major obstacles.